Protective role of Punica granatum L. peel extract against oxidative damage in experimental diabetic rats - Althunibat, Osama Yousef; H. Al-Mustafa, Ahmed; Tarawneh, Khaled; M. Khleifat, Khaled; Hashim, Ridzwan; Qaralleh, Haitham; Qaralleh, Haitham (ELSEVIER, 2010)
Punica granatum L. (Punicaceae) peels extract had the highest free radical scavenging capacity among the tested medicinal plants which are being used traditionally for treatment of diabetes in Jordan. Accordingly, the present study aimed to investigate the antioxidant effect of P. granatum peel methanolic extract against oxidative damage in streptozotocin-induced diabetic rats. The antioxidant activity of P. granatum peel extract was investigated by examining the level of antioxidant enzymes, catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione-S-transferase (GST) and glutathione reductase (GR), the serum total antioxidant capacity and lipid peroxidation in the tissues of treated diabetic rates comparing with normal and untreated diabetic ones. The results revealed that intraperitoneal administration of 10 and 20 mg kg−1 (body weight) of P. granatum peel extract for 4 weeks significantly enhanced the activities of antioxidant enzymes in liver, kidney and RBC of STZ-induced diabetic rats. The extract also caused a significant reduction in malondialdehyde (MDA), a lipid peroxide's marker, in diabetic rat tissues and elevated the total serum antioxidant capacity in dose-dependent manner. In conclusion, this study clearly showed that P. granatum peel extract has protective role against the oxidative damage in STZ-induced diabetic rats.